2010
DOI: 10.1590/s1020-49892010000200007
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose concentration and pH in liquid oral pediatric medicines of long-term use for children

Abstract: It can be concluded that the pediatric medicines studied have a high SC and low pH, which vary according to therapeutic class, daily dose, and brand. Caution about dental caries, dental erosion, and systemic diseases such as diabetes mellitus is warranted when these medicines are ingested frequently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
35
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 13 publications
6
35
1
2
Order By: Relevance
“…The erosive potential of ferrous sulfate hypothesized by Passos et al (25), was confirmed in the present research. However, most of the studies are performed on a permanent tooth substrate.…”
Section: Discussionsupporting
confidence: 90%
“…The erosive potential of ferrous sulfate hypothesized by Passos et al (25), was confirmed in the present research. However, most of the studies are performed on a permanent tooth substrate.…”
Section: Discussionsupporting
confidence: 90%
“…However, higher sugar contents were observed in other studies with percentages ranging from 65.0% [15] to 86.9% [17]. …”
Section: Discussionmentioning
confidence: 52%
“…Although the development of erosion is also influenced by the enamel type, temperature and acid exposition time (12). Passos et al (13) observed in the sample the mean ± SD of endogenous pH and compared between groups: endocrine, nutrition and blood group had lower mean (3.8 ± 1.0 and 4.3 ± 1.8, respectively), while anti-infective and cardiovasculary system group had mean pH higher than the critical value (5.5) to enamel desmineralization. The mean pH of iron sulfate had high influence on the mean pH of nutrition and blood groups (minimum and maximum pH 2.3 ± 0.01 and 3.6 ± 0.2, respectively).…”
Section: Discussionmentioning
confidence: 99%